Elmer and the rainbow - McKee, David (Minneapolis : Andersen Press USA, 2011)
Elmer the elephant enlists his animal friends to help him find the end of a strange, colorless rainbow so that he can share some of his patchwork colors and make it right.
New York Times
New York Times, March 2011
2.1
Preschool.
Preschool
Keywords: Animals -- Juvenile fiction; Elephants -- Juvenile fiction; Rainbows -- Juvenile fiction; Animals -- Fiction; Elephants -- Fiction; Rainbows -- Fiction; Animals -- Fiction; Elephants -- Fiction; Rainbow -- Fiction; Picture books for children